Pembuatan Selai Salak (Salacca edulis reinw) : Kajian Dari Penambahan Natrium Benzoat Dan Gula Yang Tepat Terhadap Mutu Selai Salak Selama Penyimpanan - Hartati, Endang Nur; Rahayuningsih, Tri; Feriyani, Nike Vinda (UPN VETERAN JAWA TIMUR, 2009)
This research aimed to define a proper concentration of preservative and sugar addedÂ for âselai salakâ storage-life. This research used random block design which wasÂ containing two factors treatment with three (3) times repeating. First factor was theÂ concentration of preservative (A1 = 0%, A2 = 0,05% and A3 = 0,1%). Second factorÂ was concentration of sugar (B1 = 55% and Â B2 = 75%. It will be analysed at first dayÂ and 30thÂ day. The parameters would be analysed were water contain and sum micro-organism, also hedonic test. Â Â The result showed that the best alternative processing of A1B2 (0% Â natriumÂ benzoat and 75% sugar) with pay off 21,91 based on product quality (water contain,Â sum micro-organism and hedonic test).Key words: âselai salakâ, preservative, polyethylene, polypropylene and vacuum